2020
DOI: 10.1111/lsq.12314
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Electoral Connection of Speeches: The Impact of Electoral Vulnerability on Legislative Speechmaking in a Preferential Voting System

Abstract: Recent literature highlights the incentives emanating from the electoral system and intraparty politics to explain unequal access to the plenary floor. This article contributes to the literature by investigating the effect of electoral vulnerability on the likelihood to deliver speeches in a preferential voting system. Drawing on data from Finland, it argues that intraparty vulnerability has a negative impact on the likelihood to deliver speeches, whereas the opposite effect is expected regarding interparty vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Previous studies have found a relationship between the extent to which legislators are likely to keep their seats in the next election (i.e. their electoral vulnerability) and the level of constituency effort – for example, the number of trips they make to their districts (André, Depauw, and Martin, 2015) or the number of speeches they deliver on the floor (Poyet and Raunio, 2021). These studies, however, say little regarding the geographical width of such effort.…”
Section: Twitter Style Constituency‐building In Multimember Systems A...mentioning
confidence: 99%
“…Previous studies have found a relationship between the extent to which legislators are likely to keep their seats in the next election (i.e. their electoral vulnerability) and the level of constituency effort – for example, the number of trips they make to their districts (André, Depauw, and Martin, 2015) or the number of speeches they deliver on the floor (Poyet and Raunio, 2021). These studies, however, say little regarding the geographical width of such effort.…”
Section: Twitter Style Constituency‐building In Multimember Systems A...mentioning
confidence: 99%
“…Past literature shows that institutional arrangements where party organizations and voters share the role of gatekeepers to elected office produce legislators who are more independent in their activities and more likely to challenge party unity when such an action promises to boost their personal credit among their constituents (Carey 2007; Carroll and Nalepa 2021; Meserve, Robbins, and Thames 2017). Candidates’ preference-vote tallies have been linked to a greater proclivity to hold speeches (Marcinkiewicz and Stegmaier 2019; Poyet and Raunio 2020), table interpellations (Louwerse and Otjes 2016), or sponsor bill proposals (Bouteca et al 2019; Crisp et al 2013). By producing MPs who are at least as attentive to the interests of their electorates as those of their party superiors, preference voting might have a capacity to give rise to party groups that less cohesive, more internally democratic and more programmatically varied (André et al 2017).…”
Section: Personal Voting and Legislator Autonomymentioning
confidence: 99%
“…This is not necessarily a measure of independent legislative activity but rather an indicator of how active each MP is in the legislature. Past literature shows that those MPs who feel that their own position is insecure submit or sponsor more bill proposals than their colleagues as a way of signaling to their primary principal that they are hard workers (Borghetto and Lisi 2018; Poyet and Raunio 2020). Independent legislative behavior is measured as a ratio between the number of submitted and successful bill proposals (Wauters, Bouteca, and de Vet 2019).…”
Section: Data Operationalization and Model Specificationmentioning
confidence: 99%
“…For our second example, we revisit Poyet and Raunio (2021) (henceforth PR), who examine the impact of electoral vulnerability on legislative speechmaking. Their main findings are that as intra‐party vulnerability (“1 minus the margin between the number of votes separating the MP and the first nonelected challenger and the total number of votes”, 13) increases, speeches by members of parliament (MP) decline.…”
Section: Example 2: Poyet and Raunio (2021)mentioning
confidence: 99%
“… Dependent variable is the number of speeches, replicating Poyet and Raunio (2021), Table 2, Model 3, in the Supporting information Appendix. Two‐tailed tests.…”
Section: Example 2: Poyet and Raunio (2021)mentioning
confidence: 99%